“Showing Up”: An Autoethnographic Exploration of Black Women’s Teaching Mentorship Narrative in Counselor Education - Brean'a M Parker; Shawntell Pace; Collette Chapman-Hilliard; Raven Cokley (Teaching and Supervision in Counseling, 2024)
While Black women are entering academe at increasing rates, they still remain underrepresented in the counselor education academic workforce. Empirical literature suggests that lack of educational infrastructure, challenging sociocultural climates and fewer possibility models within academe are factors for low matriculation of Black women doctoral students into academic positions in counselor education. Utilizing collaborative autoethnography (CAE), we explore teaching mentorship relationships among Black women (N = 4) counseling faculty and doctoral students. We also examine how mentoring relationships shape Black women’s professionalization within academe in a manner that fosters the embodiment and practice of social justice andragogy. CAE narratives revealed teaching mentorships as promoting social justice-based teaching andragogy, cultural praxis of community as liberative and providing a blueprint for transformative praxis among mentees in counselor education training programs. Implications for counselor educators from our findings identify the importance of implementing programmatic infrastructure and culturally- responsive mechanisms to be considered in support of Black women students’ matriculation into academe
Keywords: mentorship; counselor education; psychology; teaching; Black women